Formulation and Evaluation of Herbal Nail Polish That Dissolves and Detect Alcohol in Beverages: A Safety Measure for Women - P. Patel, Arshu; N. Kharde, Shekhar; R. Kasar, Harshal; R. Varpe, Tanmay; R. Kudnar, Jagdish; G. Bhosale, Shainesh; P. Shinde, Nayan; S. Kamble, Rutuja; A. Jondhale, Tejal (Journal of Neonatal Surgery, 2025)
ABSTRACT Background: Spiking of drinks has emerged as a serious safety issue, especially among women in social settings. Unreliable and discreet detection mechanisms increase susceptibility. For this purpose, this study is aimed at designing a herbal nail polish that is soluble on coming into contact with alcoholic drinks, providing a novel safety solution [1]. Objective: The major objective of this research is to develop and assess a herbal nail polish that can sense alcohol by dissolving and emitting a noticeable color shift. This is a product that combines beauty with utility, which gives a handy but easy tool for personal safety [2]. Materials and Methods: The nail polish was developed based on Polyvinyl Alcohol (PVP), Dragon Fruit Extract, Coconut Oil, Castor Oil, and Rose Oil, for safety, eco-friendliness, and efficacy [3,4]. PVP acts as the base polymer, soluble in alcohol, while Dragon Fruit Extract is used as a natural coloring agent [5]. The product was tested for alcohol sensitivity, stability, and safety by way of dissolution, patch, and stability tests [6]. Results: The nail polish effectively dissolved in 5-10 seconds when exposed to alcohol, emitting a clear colour signal. Stability tests validated its resistance in non-alcoholic environments, and safety tests proved non-toxic and skin-friendly qualities [7]. Conclusion: This herbal nail polish presents an efficient, environmentally friendly, and novel solution to drink safety. By combining cosmetic functionality with protective functions, the study offers a handy solution for improving women's safety and pointing out the possibility of science-based innovations in beauty products [9,10].